Higher education’s impact on CO2 mitigation: MENA insights with consideration for unemployment, economic growth, and globalization - Zouine, Marouane; EL Adnani, Mohamed Jallal; Salhi, Salah Eddine (Frontiers in Environmental Science, 2024)
This study investigates the intricate interplay between higher education and environmental pollution in the MENA region from 2000 to 2018. Employing a comprehensive analytical approach, including cross-dependency tests alongside panel unit root tests, Kao cointegration tests, fixed effect GLS, DOLS (dynamic ordinary least squares), FMOLS (fully modified ordinary least squares) estimations, and Granger causality tests, the research focuses on three critical control variables-Unemployment, gross domestic product, and the globalization index. The main findings, derived from GLS analysis, reveal a positive correlation between higher education, globalization, and GDP per capita with CO2 emissions in the MENA region. However, delving deeper using DOLS and FMOLS, a nuanced perspective emerges. While GDP per capita appears to contribute to increased CO2 emissions, other variables, notably higher education and globalization, play a pivotal role in mitigating CO2 emissions in the long run. This challenges the prevailing Kuznets curve hypothesis, confirming its applicability for education but raising questions for economic growth in MENA countries. Furthermore, the results from the FMOLS estimation, akin to DOLS, demonstrate similar outcomes, reaffirming the robustness of the findings regarding the impact of higher education, globalization, and economic factors on CO2 emissions in the MENA region. Additionally, the causality tests provide insights into the directional relationships between variables, highlighting the significant role of higher education and globalization in influencing CO2 emissions. These findings address a critical gap in the understanding of environmental dynamics in the MENA region and offer valuable insights for policymakers and governments. The nuanced understanding of the impact of higher education, globalization, and economic factors can inform targeted interventions and policies, contributing to sustainable development and reduced CO2 emissions in the MENA region.